Privacy and Identity Management: The Smart Revolution : 12th IFIP WG 9.2, 9.5, 9.6/11.7, 11.6/SIG 9.2.2 International Summer School, Ispra, Italy, September 4-8, 2017, Revised Selected Papers - Hansen, Marit; Kosta, Eleni; Nai-Fovino, Igor; Fischer-Hubner, Simone (Privacy and Identity Management. The Smart Revolution 12th IFIP WG 9.2, 9.5, 9.6/11.7, 11.6/SIG 9.2.2 International Summer School, Ispra, Italy, September 4-8, 2017, Revised Selected Papers, 2018)
This book contains selected papers presented at the 12th IFIP WG 9.2, 9.5, 9.6/11.7, 11.6/SIG 9.2.2 International Summer School on Privacy and Identity Management, held in Ispra, Italy, in September 2017.The 12 revised full papers, 5 invited papers and 4 workshop papers included in this volume were carefully selected from a total of 48 submissions and were subject to a three-phase review process. The papers combine interdisciplinary approaches to bring together a host of perspectives: technical, legal, regulatory, socio-economic, social, societal, political, ethical, anthropological, philosophical, and psychological. They are organized in the following topical sections: privacy engineering; privacy in the era of the smart revolution; improving privacy and security in the era of smart environments; safeguarding personal data and mitigating risks; assistive robots; and mobility and privacy.